Advancements and Frontiers in the High Performance of Natural Hydrogels for Cartilage Tissue Engineering - Bao, Wuren; Li, Menglu; Yang, Yanyu; Wan, Yi; Wang, Xing; Bi, Na; Li, Chunlin (Frontiers in Chemistry, 2020)
Cartilage injury originating from the trauma or osteoarthritis is a common joint disease that can bring about an inescapably increasing social and economic burden in modern society. On account of its avascular, neural and lymphatic characteristics, poor migration ability of chondrocytes and a low number of progenitor cells, the self-healing ability of cartilage defects has been significantly limited. Natural hydrogels, occurred abundantly with many characteristics of high-water content, biodegradation, porosity and biocompatibility similar to the natural extracellular matrix, have been developed into one of the most suitable scaffold biomaterials for the regeneration of cartilage in material science and tissue engineering. Notably, natural hydrogels possessed bionic mechanical behaviors of physiological cartilage that required for usage as the articular cartilage substitutes, by which the enhanced chondrogenic phenotype ability may be achieved by facilely embedding living cells, controlling degradation profiles and releasing stimulatory growth factors. Hence, we summarize an overview of strategies and developments of various kinds and functions of natural hydrogels for cartilage tissue engineering in this review. Furthermore, the essential concepts and recent discoveries were also demonstrated to illustrate the achievable goals, current limitations and major challenges, such as the vascularity, clinically relevant size and mechanical properties that need to be addressed to successfully make use of the advanced technologies in clinical settings. In addition, we propose the putative challenges and directions for the ongoing preclinical research trials in cartilage regeneration using hydrogel scaffolds, and the challenges and future prospects of research in the regenerative medicine ﬁeld are also presented. Therefore, the grand aim of this review is to underpin the importance of synthesis, modiﬁcation and application of the natural hydrogels for cartilage tissue engineering, which has been achieved by presenting a promising avenue in multifarious fields and postulating their real-world respective potentials.